Inducible renal principal cell-specific mineralocorticoid receptor gene inactivation in mice - Ronzaud, Caroline; Loffing, Johannes; Gretz, Norbert; Schütz, Günther; Berger, Stefan (American journal of physiology. Renal physiology, 2011)
To investigate the role of the mineralocorticoid receptor (MR) in renal ENaC-mediated sodium reabsorption, we have previously used the Cre-loxP system to generate mice with principal-cell specific MR ablation (MRAQP2Cre mice). To restrict Cre expression to principal cells, we have used the regulatory elements of the mouse aquaporin-2 (AQP2) gene to drive Cre expression. Since AQP2 is already expressed during renal development, MR ablation took place long before the analysis performed at the adult stage. To investigate whether the early onset of MR ablation affected the adult renal sodium handling, we developed a transgene expressing the CreERT2 fusion protein under control of the regulatory elements of the AQP2 gene (AQP2CreERT2). Immunofluorescence revealed MR loss in the collecting duct (CD) and late connecting tubule after induction of MR ablation by tamoxifen in MRAQP2CreERT2 mice that equals the MR loss in MRAQP2Cre mice. Surprisingly, tamoxifen-independent MR loss is observed in CDs of noninduced mutants without affecting circulating aldosterone levels. Under a low-salt diet, the induced ablation of MR at the adult stage recapitulates the renal sodium wasting observed in mice with constitutive early-onset MR ablation. The AQP2CreERT2 transgene is a new tool for investigating in vivo the function of genes downstream of MR in renal ENaC-mediated sodium reabsorption by inducible somatic gene inactivation.